Penyakit Malaria dan Faktor Risikonya - Wanti Wanti; Stephani Mangi; Oktovianus Sila; Johanes P. Sadukh; Irfan Irfan (Jurnal Riset Kesehatan, 2015)
This analytic observational research used case control study with the research variables are knowledge, attitude, practice, and breeding place distance. All of the positive malaria patients are used as case group that are 32 people and as a control group used 32 healthy people around the case group. The data were collected by applying interview and observation and then data be analysed using chi square (α 0,05) to know the relation between the independent and dependent variables. The research result shows there are relation between the malaria prevalence with attitude (ρ 0,017), practice (ρ 0,013), and breeding palce distance (ρ=0,000). The conclusion is that the good knowledge can not influence the community to have a good attitude and to apply in daily life to do malaria combating. It is important to do health promotion of malaria especially to improve the knowledge and to apply their knowledge in daily activities to combat the malaria disease.